Making up for the munchies? Examining cannabis-related eating and compensatory behaviors among undergraduates - Pince, Claire L., author; Emery, Noah, advisor; Karoly, Hollis, advisor; Schomaker, Lauren, committee member; Amberg, Marti, committee member (Colorado State University. Libraries, 2025)
Food and alcohol disturbance (FAD) refers to a phenomenon whereby individuals engage in compensatory behaviors such as caloric restriction, exercise, or purging to offset calories associated with alcohol consumption or to enhance the effects of alcohol. FAD is well-documented amongst college student populations in the United States, however, there remains a gap in the literature with regards to compensatory behaviors in response to other types of substance use, such as cannabis. Cannabis use has become increasingly prevalent among U.S. college students in the past decade, coincident with recent trends towards recreational legalization. Cannabis interacts with the endogenous cannabinoid system (ECS), which plays a critical role in regulating appetite and energy balance, and many individuals who use cannabis report increased appetite or motivation for food, colloquially referred to as "the munchies." Existing literature on the relationship between cannabis use and disordered eating behaviors is limited in scope and has yielded mixed findings, and no study to date has specifically examined engagement in cannabis-related compensatory behaviors in undergraduate populations. Overall, the aims of this study were to (1) develop a measure of compensatory behaviors in response to cannabis use (2) examine associations between engagement in cannabis compensatory behaviors and eating disorder symptomatology, consequences related to cannabis use, and binge eating under the influence of cannabis. The Compensatory Eating and Behaviors in Response to Alcohol Consumption Scale (CEBRACS) was adapted with a focus on cannabis use and "the munchies" and survey items were piloted in a sample of undergraduates at Colorado State University. Modifications were made to survey items and formatting according to pilot participant and subject matter expert feedback. Participants (n = 519) were subsequently recruited from undergraduate samples at Colorado State University and the University of Wyoming (mid-size and large, legal and non-legal recreational status) and completed the final survey in addition to measures related to cannabis use frequency, eating disorder symptoms, and binge eating under the influence of cannabis. Exploratory and confirmatory analyses were utilized to identify the underlying structure of the scale and yielded three factors consistent with previous FAD literature: Enhancement, Diet/Exercise Compensation, and Extreme Weight Loss Behaviors (EWLB). Binge eating under the influence of cannabis was positively associated with all three factors but eating disorder symptoms were only significantly associated with the Diet/Exercise factor. Enhancement and Diet/Exercise Compensation factors were positively associated with cannabis consequences after controlling for covariates, whereas there was a negative relationship for the EWLB factor, which was shown to be mediated through reduced cannabis use frequency. Findings from the present study provides initial evidence for the adaptation and validation of a three-factor Compensatory Eating and other Behaviors in Response to Cannabis Scale (CECBS), furthermore highlighting nuanced relationships between cannabis-related compensatory behaviors and eating disorder symptomatology, cannabis-related binge eating, and cannabis consequences, which may have important clinical implications for cannabis harm reduction as well as the prevention and treatment of cannabis use disorder and eating disorders.